Secondary batteries and devices
By regulating the sulfur content and material matching relationship in lithium iron phosphate batteries, the safety problem of iron ion dissolution during battery circulation is solved, and the circulation performance and safety of the battery are significantly improved.
Patent Information
- Application Number
- CN202311694010.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-08
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2043-12-08
AI Technical Summary
During the circulation process of existing lithium iron phosphate batteries, the dissolution of the positive electrode side iron ions causes serious erosion and damage to the negative electrode sheet, which has serious safety problems.
By regulating the sulfur content in the interface film of positive and negative electrode solid electrolytes, the matching relationship between lithium iron phosphate materials in the positive electrode sheet and sulfur-containing additives in the electrolyte, the specific sulfur content range is met to improve the stability of positive and negative electrode film formation and reduce the dissolution and corrosion of iron ions.
The cycling performance and safety of the secondary battery are significantly improved, the dissolution of the positive electrode side iron ions and the erosion of the negative electrode sheet are reduced, the gas production problem is improved, and the impedance is reduced.
Smart Images

Figure BDA0004604697970000121 
Figure BDA0004604697970000131 
Figure BDA0004604697970000141
Abstract
Description
Technical Field
[0001] The present application relates to the field of energy storage, and in particular to a secondary battery and a device. Background Art
[0002] With the development of society, the demand for lithium-ion batteries in application fields such as smart phones, unmanned aerial vehicles, and hybrid electric vehicles is increasing, but the energy density of existing lithium-ion batteries can no longer meet the demand. Therefore, the development of high-capacity and high-safety battery systems has become a research direction for lithium-ion batteries. Lithium iron phosphate batteries are widely used in the field of power and energy storage batteries due to their high thermal stability and long life. However, during the research process, it was found that during the cycle of existing lithium iron phosphate batteries, the dissolution of iron ions on the positive electrode side causes serious erosion and damage to the negative electrode sheet, posing serious safety problems. Therefore, in order to solve the above-mentioned problems of lithium iron phosphate batteries, it is necessary to develop a new type of battery system, in which the interaction between the electrolyte, the interface film and the electrode material needs to be studied in depth. Summary of the invention
[0003] In view of the above problems existing in the prior art, the present application proposes a secondary battery and device. The present application improves the stability of positive and negative electrode film formation, improves the dissolution of iron ions on the positive electrode side, and avoids the corrosion and damage of the negative electrode by iron ions after dissolution, improves the gas production problem of the secondary battery, reduces impedance, and improves the cycle performance and safety of the secondary battery by regulating the sulfur content in the positive and negative electrode solid electrolyte interface films, the matching relationship between the lithium iron phosphate material in the positive electrode plate and the sulfur-containing additive in the electrolyte.
[0004] The first aspect of the present application provides a secondary battery, which includes a positive electrode plate, a negative electrode plate and an electrolyte, wherein the positive electrode plate includes a positive electrode active material layer and a positive electrode solid electrolyte interface membrane located on the surface of the positive electrode active material layer; the negative electrode plate includes a negative electrode active material layer and a negative electrode solid electrolyte interface membrane located on the surface of the negative electrode active material layer; the positive electrode active material layer includes a positive electrode active material, the positive electrode active material includes a lithium iron phosphate material, and the electrolyte includes a sulfur-containing additive, wherein every 100g Fe corresponds to Zg of the sulfur-containing additive; using an X-ray photoelectron spectrometer to test, the mass percentage of sulfur element in the positive electrode solid electrolyte interface membrane is Y1%, and the mass percentage of sulfur element in the negative electrode solid electrolyte interface membrane is Y2%; the secondary battery satisfies the following: (1) 0.8≤Y1+Y2≤8.0; (2) 1.0≤(Y1+Y2) / Z≤3.5.
[0005] A second aspect of the present application provides a device including the aforementioned secondary battery.
[0006] The technical solution of this application can achieve the following beneficial effects:
[0007] The present application adjusts the sulfur content in the positive electrode solid electrolyte interface film (CEI), the sulfur content in the negative electrode solid electrolyte interface film (SEI), the matching relationship between the lithium iron phosphate material in the positive electrode plate and the sulfur-containing additive in the electrolyte, so as to simultaneously satisfy 0.8≤Y1+Y2≤8.0 and 1.0≤(Y1+Y2) / Z≤3.5. Under this limited condition, the film formation stability of the positive and negative electrodes can be improved, the dissolution of iron ions on the positive electrode side can be improved, and the erosion and damage of the negative electrode plate by iron ions after dissolution can be avoided. At the same time, the gas production problem of the secondary battery is improved and the impedance is reduced, thereby improving the cycle performance and safety of the secondary battery with lithium iron phosphate materials as the main material. DETAILED DESCRIPTION
[0008] In order to make the purpose, technical scheme and advantages of the present application clearer, the technical scheme of the present application will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present application, rather than all the embodiments. The relevant embodiments described herein are illustrative and are used to provide a basic understanding of the present application. The embodiments of the present application should not be interpreted as limiting the present application.
[0009] For simplicity, only some numerical ranges are specifically disclosed herein. However, any lower limit can be combined with any upper limit to form an unspecified range; and any lower limit can be combined with other lower limits to form an unspecified range, and any upper limit can be combined with any other upper limit to form an unspecified range. In addition, each separately disclosed point or single value can itself be combined as a lower limit or upper limit with any other point or single value or with other lower limits or upper limits to form an unspecified range.
[0010] In the description herein, unless otherwise specified, “above” and “below” include the number.
[0011] Unless otherwise specified, the terms used in this application have the commonly known meanings generally understood by those skilled in the art. Unless otherwise specified, the numerical values of the various parameters mentioned in this application can be measured using various measurement methods commonly used in the art (for example, they can be tested according to the methods given in the examples of this application).
[0012] A list of items connected by the terms "at least one of," "at least one of," "at least one of," or other similar terms may mean any combination of the listed items. For example, if items A and B are listed, the phrase "at least one of A and B" means only A; only B; or A and B. In another example, if items A, B, and C are listed, the phrase "at least one of A, B, and C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may contain a single component or multiple components. Item B may contain a single component or multiple components. Item C may contain a single component or multiple components.
[0013] Primary and secondary batteries
[0014] One or more embodiments of the present application provide a secondary battery, which includes a positive electrode plate, a negative electrode plate and an electrolyte, wherein the positive electrode plate includes a positive electrode active material layer and a positive electrode solid electrolyte interface membrane located on the surface of the positive electrode active material layer; the negative electrode plate includes a negative electrode active material layer and a negative electrode solid electrolyte interface membrane located on the surface of the negative electrode active material layer; the positive electrode active material layer includes a positive electrode active material, the positive electrode active material includes a lithium iron phosphate material, and the electrolyte includes a sulfur-containing additive, wherein every 100g of Fe corresponds to Zg of the sulfur-containing additive; using an X-ray photoelectron spectrometer to test, the mass percentage of sulfur element in the positive electrode solid electrolyte interface membrane is Y1%, and the mass percentage of sulfur element in the negative electrode solid electrolyte interface membrane is Y2%; the secondary battery satisfies the following conditions: (1) 0.8≤Y1+Y2≤8.0; (2) 1.0≤(Y1+Y2) / Z≤3.5.
[0015] The present application adjusts the matching relationship between the sulfur content in the CEI film, the sulfur content in the SEI film, the lithium iron phosphate material in the positive electrode plate and the sulfur-containing additive in the electrolyte to simultaneously satisfy 0.8≤Y1+Y2≤8.0 and 1.0≤(Y1+Y2) / Z≤3.5. Under this limited condition, the film formation stability of the positive and negative electrodes can be improved, the dissolution of iron ions on the positive electrode side can be improved, and the erosion and damage of the negative electrode plate by iron ions after dissolution can be avoided. At the same time, the gas production problem of the secondary battery can be improved and the impedance can be reduced, thereby improving the cycle performance and safety of the secondary battery with lithium iron phosphate materials as the main material.
[0016] In some embodiments, 0.8≤Y1+Y2≤8.0. If the value of Y1+Y2 is too low, the CEI film and SEI film formed on the electrode surface will be loose and porous and not dense enough, and a stable interface film cannot be formed, which will affect the electrical performance and safety of the secondary battery; if the value of Y1+Y2 is too high, the CEI film and SEI film formed on the electrode surface will be too thick and prone to uneven distribution. An excessively thick interface film will bring a higher interface impedance (DCR), which will deteriorate the kinetic performance of the secondary battery. At the same time, an unevenly distributed interface film will also easily cause lithium deposition problems in the battery core, resulting in a decrease in the performance of the secondary battery, a significant decrease in the cycle capacity retention rate, and even affecting the safety performance of the secondary battery; therefore, limiting Y1+Y2 to the above range is conducive to improving the cycle performance and safety of the secondary battery. In some embodiments, Y1+Y2 is 0.8, 1.0, 1.2, 1.4, 1.6, 1.8, 2.0, 2.2, 2.4, 2.6, 2.8, 3.0, 3.2, 3.4, 3.6, 3.8, 4.0, 4.2, 4.4, 4.6, 4.8, 5.0, 5.2, 5.4, 5.6, 5.8, 6.0, 6.2, 6.4, 6.6, 6.8, 7.0, 7.2, 7.4, 7.6, 7.8, 8.0, or a range consisting of any two of the above values.
[0017] In some embodiments, 1.0≤Y1+Y2≤6.0. Within this limited range, an excellent CEI / SEI film with low impedance and high density can be further formed, which is more conducive to improving the electrical performance and safety of the secondary battery.
[0018] In some embodiments, 1.0≤(Y1+Y2) / Z≤3.5. The value of (Y1+Y2) / Z is too low, indicating that the sum of the sulfur-containing compound content of the CEI film and the sulfur-containing compound content in the SEI film in the positive electrode cell with lithium iron phosphate as the main material is too low, which cannot effectively prevent the dissolution of iron ions on the positive electrode side, and cannot effectively protect the negative electrode plate structure, which seriously affects the cycle performance and safety performance of the secondary battery; the value of (Y1+Y2) / Z is too high, indicating that the sum of the sulfur-containing compound content of the CEI film and the sulfur-containing compound content in the SEI film in the positive electrode cell with lithium iron phosphate as the main material is too high, thereby deteriorating the transmission efficiency of lithium ions at the interface and affecting the kinetic performance of the secondary battery; therefore, limiting (Y1+Y2) / Z within the above range is conducive to improving the cycle performance, safety and kinetic performance of the secondary battery. In some embodiments, (Y1+Y2) / Z is 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0, 3.1, 3.2, 3.3, 3.4, 3.5 or a range consisting of any two of the above values.
[0019] In some embodiments, 1.5≤(Y1+Y2) / Z≤3.0. Within this limited range, the positive electrode materials with different Fe contents can be better matched, the formed CEI film more effectively protects the positive electrode sheet structure and inhibits the dissolution of iron ions, and the SEI film more effectively protects the negative electrode sheet structure, further improving the electrical performance and safety of the secondary battery.
[0020] In some embodiments, 0.1≤Y1≤2.5. If Y1 is too high, the impedance of the CEI film will be too high, thereby deteriorating the lithium ion transmission capacity of the interface film, that is, deteriorating the kinetic performance of the lithium ion battery; if Y1 is too low, the CEI film will be non-dense and incomplete, and the electrode material cannot be effectively protected, that is, the safety performance of the battery cell cannot be effectively guaranteed; controlling Y1 within the above range can improve the kinetic performance of the lithium ion battery while ensuring its safety performance. In some embodiments, Y1 is 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5 or a range consisting of any two of the above values. In some embodiments, 0.3≤Y1≤2.0.
[0021] In some embodiments, 0.3≤Y2≤6.0. If Y2 is too high, the impedance of the SEI film will be too high, thereby deteriorating the lithium ion transmission capacity of the interface film, that is, deteriorating the kinetic performance of the lithium ion battery; if Y2 is too low, the SEI film will be loose and incomplete, and the electrode material cannot be effectively protected, that is, the safety performance of the battery cell cannot be effectively guaranteed; controlling Y2 within the above range can improve the kinetic performance of the lithium ion battery while ensuring its safety performance. In some embodiments, Y2 is 0.3, 0.5, 1.0, 1.5, 2.0, 2.5, 3.0, 3.5, 4.0, 4.5, 5.0, 5.5, 6.0 or a range consisting of any two of the above values. In some embodiments, 0.5≤Y2≤5.0.
[0022] In some embodiments, 0.1≤Z≤5.0. If Z is too high, the amount of sulfur-containing additive introduced is too high, which will make the SEI / CEI film too thick and the impedance too large; if Z is too low, the amount of sulfur-containing additive introduced is too low, which will make the formed SEI / CEI film insufficient in integrity and unable to effectively protect the electrode material. In some embodiments, Z is 0.1, 0.5, 1.0, 1.5, 2.0, 2.5, 3.0, 3.5, 4.0, 4.5, 5.0 or a range consisting of any two of the above values. In some embodiments, 0.3≤Z≤4.0.
[0023] In some embodiments, the sulfur-containing additive includes at least one of sulfonate, sulfate and sulfite. The sulfur-containing additive has a lower reduction potential and can form inorganic sulfur-based lithium salts such as Li2S, Li2SO4, Li3SO3 and organic compound segments such as alkanes, alkenes, alkynes and the like with different segment lengths in the formation stage of the low voltage segment, and participate in the formation of the interface film on the electrode surface, thereby improving the interface stability and the interface lithium conductivity, and further improving the electrical performance and safety of the battery cell.
[0024] In some embodiments, the sulfonate ester includes at least one of 1,3-propane sultone (1,3-PS), 1-propylene-1,3-sultone (PST), 1,4-butane sultone (1,4-BS), and methylene methyl disulfonate (MMDS).
[0025] In some embodiments, the sulfate ester includes at least one of diethylene sulfate (DTD), 4-methylethylene sulfate (PCS), 4-ethylethylene sulfate (PES), 4-propylethylene sulfate (PEGLST), and propylene sulfate (TS).
[0026] In some embodiments, the sulfite includes at least one of ethylene sulfite (DTO), dimethyl sulfite (DMS), and diethyl sulfite (DES).
[0027] In some embodiments, the lithium iron phosphate material includes Li x Fe y R (1-y) At least one of PO4 materials, wherein R includes at least one of Mn, Co, Ti, Mg, Ca, Cr, Cu, Ni, V, Mo, Zn, Al, B and Nb elements, 0.05≤x≤1.2, 0<y≤1.
[0028] In some embodiments, the lithium iron phosphate-based material is preferably LiFePO4.
[0029] In some embodiments, the surface of the lithium iron phosphate material has a carbon coating layer; based on the mass of the lithium iron phosphate material, the mass percentage of the carbon coating layer is 1% to 3%. It is understandable that if the carbon coating layer is too thin, it will not effectively improve the inherent conductivity of the positive electrode material, and the power performance of the lithium-ion battery will be poor; if the carbon coating layer is too thick, the energy density of the lithium-ion battery will be significantly reduced, and the non-uniformity of the coating will be more obvious and the defects will increase, affecting the performance of the lithium-ion battery. In some embodiments, the mass percentage of the carbon coating layer is 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3.0% or a range consisting of any two of the above values.
[0030] In some embodiments, the positive electrode active material layer further includes a binder, and optionally a conductive material. The binder improves the bonding between the positive electrode active material particles and also improves the bonding between the positive electrode active material and the current collector.
[0031] In some embodiments, the binder includes, but is not limited to: polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylated styrene-butadiene rubber, epoxy resin or nylon, etc.
[0032] In some embodiments, the conductive material includes, but is not limited to: carbon-based materials, metal-based materials, conductive polymers, and mixtures thereof. In some embodiments, the carbon-based material is selected from natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, or any combination thereof. In some embodiments, the metal-based material is selected from metal powder, metal fiber, copper, nickel, aluminum, or silver. In some embodiments, the conductive polymer is a polyphenylene derivative.
[0033] In some embodiments, the positive electrode plate further includes a positive current collector, which may be a metal foil or a composite current collector. For example, aluminum foil may be used. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver, silver alloy, etc.) on a polymer substrate.
[0034] In some embodiments, the porosity of the positive electrode sheet is ε1, which satisfies: 22% ≤ ε1 ≤ 42%. If the porosity of the positive electrode sheet is too low, it will affect the infiltration of the electrolyte, resulting in too low sulfur content in the CEI membrane and increasing the difficulty of lithium ion conduction; if the porosity of the positive electrode sheet is too high, it will damage the energy density of the positive electrode sheet. Controlling the porosity of the positive electrode sheet within the above range is conducive to controlling the sulfur content in the CEI membrane within a reasonable range while ensuring a high energy density, and ensuring the rapid conduction of lithium ions in the positive electrode sheet. In some embodiments, ε1 is 22%, 24%, 26%, 28%, 30%, 32%, 34%, 36%, 38%, 40%, 42% or a range consisting of any two of the above values.
[0035] In some embodiments, the negative electrode active material layer includes a negative electrode active material, and the negative electrode active material includes at least one of a silicon-based material, a carbon-based material, a tin-based material, a phosphorus-based material, and metallic lithium. Exemplarily, the silicon-based material includes at least one of silicon, a silicon alloy, a silicon oxide compound, and a silicon carbon compound. Exemplarily, the carbon-based material includes at least one of graphite, soft carbon, hard carbon, carbon nanotubes, and graphene. Exemplarily, the tin-based material includes at least one of tin, tin oxide, and a tin alloy. Exemplarily, the phosphorus-based material includes at least one of phosphorus and a phosphorus complex.
[0036] In some embodiments, the negative electrode active material layer also includes a binder and a conductive agent. The binder includes, but is not limited to: polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers containing ethylene oxide, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene 1,1-difluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylic (ester) styrene-butadiene rubber, epoxy resin or nylon, etc. At least one of the conductive agent includes, but is not limited to: at least one of carbon-based materials, metal-based materials, conductive polymers and mixtures thereof. In some embodiments, the carbon-based material includes natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber or any combination thereof. In some embodiments, the metal-based material includes metal powder, metal fiber, copper, nickel, aluminum or silver. In some embodiments, the conductive polymer includes a polyphenylene derivative.
[0037] In some embodiments, the negative electrode plate further includes a negative electrode current collector, which includes at least one of copper foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, a polymer substrate coated with a conductive metal, or any combination thereof.
[0038] In some embodiments, the porosity of the negative electrode sheet is ε2, which satisfies: 28% ≤ ε2 ≤ 45%. If the porosity of the negative electrode sheet is too low, it will affect the infiltration of the electrolyte, resulting in too low sulfur content in the SEI film and increasing the difficulty of lithium ion conduction; if the porosity of the negative electrode sheet is too high, it will damage the energy density of the negative electrode sheet. Controlling the porosity of the negative electrode sheet within the above range is conducive to controlling the sulfur content in the SEI film within a reasonable range while ensuring a higher energy density, and ensuring the rapid conduction of lithium ions in the negative electrode sheet. In some embodiments, ε2 is 28%, 30%, 32%, 34%, 36%, 38%, 40%, 42%, 44%, 45% or a range consisting of any two of the above values.
[0039] In some embodiments, the electrolyte further comprises a lithium salt, at least one of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium trifluorosulfonyl (LiOTf), lithium bis(oxalatoborate) (LiBOB), lithium bis(fluoromalonate) borate (LiBFMB) and lithium difluorooxalatoborate (LiDFOB). In some embodiments, the lithium salt is preferably LiPF6.
[0040] In some embodiments, the electrolyte further includes a non-aqueous solvent, and the non-aqueous solvent includes at least one of a linear carbonate compound, a cyclic carbonate compound, and a carboxylate compound.
[0041] In some embodiments, the linear carbonate compound includes, but is not limited to, one or more of dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methylpropyl carbonate (MPC), ethylpropyl carbonate (EPC), or ethylmethyl carbonate (MEC).
[0042] In some embodiments, the cyclic carbonate compound includes, but is not limited to, one or more of ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), or vinyl ethylene carbonate (VEC).
[0043] In some embodiments, the carboxylate compound includes, but is not limited to, one or more of methyl formate, methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, decanoic acid, valerolactone, or caprolactone.
[0044] In some embodiments, a separator is provided between the positive electrode and the negative electrode to prevent short circuit. The material and shape of the separator that can be used in the embodiments of the present application are not particularly limited, and it can be any technology disclosed in the prior art. In some embodiments, the separator includes a polymer or an inorganic substance formed of a material that is stable to the electrolyte of the present application.
[0045] In some embodiments, the isolation film includes a base film and a coating disposed on the base film, the base film includes at least one of a polyethylene film, a polypropylene film, a PP / PE / PP composite film, a polyimide film, an aramid film, a polyethylene terephthalate film, or a non-woven fabric. In some embodiments, the coating includes at least one of a polymer layer, an inorganic ceramic layer, or a mixed layer of a polymer and an inorganic ceramic layer.
[0046] In some embodiments, the inorganic ceramic layer includes inorganic particles and a binder, the inorganic particles include at least one of aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide, or barium sulfate. The binder includes at least one of polyvinylidene fluoride, a copolymer of vinylidene fluoride and hexafluoropropylene, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylate, polyvinylpyrrolidone, polyvinyl ether, polymethyl methacrylate, polytetrafluoroethylene, or polyhexafluoropropylene.
[0047] The polymer layer contains polymers, and the polymer material includes at least one of polyamide, polyacrylonitrile, acrylate polymer, polyacrylic acid, polyacrylate, polyvinylpyrrolidone, polyvinyl ether, polyvinylidene fluoride or poly(vinylidene fluoride-hexafluoropropylene).
[0048] In some embodiments, the preparation method of the secondary battery includes providing an electrode assembly, injecting, packaging and forming. In some embodiments, the temperature of the formation is 40°C to 50°C, for example, 40°C, 41°C, 42°C, 43°C, 44°C, 45°C, 46°C, 47°C, 48°C, 49°C, 50°C or a range consisting of any two of the above values.
[0049] In some embodiments, the formation includes: charging at a constant current of 0.05C for 120 minutes, charging at a constant current and voltage of 0.1C to 3.8V, and discharging at a constant current and voltage of 0.2C to 2.3V, at a temperature of 40°C-50°C, such as 45°C, and a pressure of 150kgf-250kgf, such as 210kgf.
[0050] In some embodiments, the secondary battery is a lithium secondary battery or a sodium secondary battery. In some embodiments, the lithium secondary battery includes, but is not limited to: a lithium metal secondary battery, a lithium ion secondary battery, a lithium polymer secondary battery, or a lithium ion polymer secondary battery.
[0051] In some embodiments, the secondary battery may include an outer package, which may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer package of the secondary battery may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, such as one or more of polypropylene (PP), polybutylene terephthalate (PBT), polybutylene succinate (PBS), etc.
[0052] In some embodiments, the shape of the secondary battery is not particularly limited, and it can be cylindrical, square, or any other shape.
[0053] In some embodiments, the present application also provides a battery module. The battery module includes the above-mentioned secondary battery. The battery module of the present application uses the above-mentioned secondary battery, and therefore has at least the same advantages as the secondary battery. The number of secondary batteries contained in the battery module of the present application can be multiple, and the specific number can be adjusted according to the application and capacity of the battery module.
[0054] In some embodiments, the present application further provides a battery pack, which includes the above-mentioned battery module. The number of battery modules contained in the battery pack can be adjusted according to the application and capacity of the battery pack.
[0055] 2. Device
[0056] The present application also provides a device, which includes at least one of the above-mentioned secondary battery, battery module or battery pack.
[0057] In some embodiments, the device includes, but is not limited to: electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, power storage systems, etc. In order to meet the device's requirements for high power and high energy density of secondary batteries, a battery pack or battery module may be used.
[0058] In other embodiments, the device may be a mobile phone, a tablet computer, a notebook computer, etc. The device is usually required to be thin and light, and a secondary battery may be used as a power source.
[0059] Hereinafter, the secondary battery of the present application will be further described in combination with specific embodiments and comparative examples.
[0060] Examples and Comparative Examples
[0061] Hereinafter, the present application will be described in more detail with reference to Examples and Comparative Examples, but the present application is not limited to these Examples unless departing from the gist of the present application.
[0062] The materials and solvents used in the following examples are all commercially available.
[0063] Example 1
[0064] Preparation of positive electrode sheet: The positive electrode active material LiFePO4 (carbon coated), conductive agent carbon nanotube (CNT) and acetylene black (ACET), and binder polyvinylidene fluoride (PVDF) are fully slurried in an N-methylpyrrolidone (NMP) solvent system at a weight ratio of LiFePO4: CNT: ACET: PVDF = 97: 0.5: 1: 1.5, and then evenly coated on one side of a positive electrode current collector aluminum foil with a thickness of 12 μm. After drying, the above steps are repeated on the other side of the aluminum foil to obtain a double-sided coated positive electrode sheet, which is then cold pressed, cut, and welded to the pole ears to obtain a positive electrode sheet.
[0065] Preparation of negative electrode sheet: The negative electrode active material graphite, conductive agent acetylene black (ACET), binder styrene butadiene rubber (SBR), thickener sodium carboxymethyl cellulose CMCNa, and polyacrylic acid PAA are fully homogenized in deionized water in a weight ratio of graphite:ACET:SBR:CMCNa:PAA=95:2:1.5:1:0.5, and then coated on one side of the negative electrode current collector copper foil with a thickness of 8 μm. After drying, the above steps are repeated on the other side of the copper foil to obtain a double-sided coated negative electrode sheet, which is then cold pressed, cut, and welded to the pole ears to obtain the negative electrode sheet.
[0066] Preparation of electrolyte: In an argon-protected glove box (water content <0.1ppm, oxygen content <0.1ppm), solvents ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) are mixed in a mass ratio of EC:EMC:DEC=3:5:2, and lithium hexafluorophosphate (LiPF6) is added to a molar concentration of 1 mol / L (mass percentage of 12.5%) based on the mass of the solvent. Based on the mass of Fe in the positive electrode sheet, a corresponding proportion of sulfur-containing additives is added to the electrolyte, and the electrolyte is prepared after stirring evenly.
[0067] Isolation film: PP / PE / PP three-layer composite film is used as the isolation film.
[0068] Preparation of lithium-ion battery: stack the prepared positive electrode sheet, separator, and negative electrode sheet in order, so that the separator is in the middle of the positive and negative electrode sheets, and wind them to obtain a bare battery cell; place the bare battery cell in an aluminum-plastic film outer package, and inject the prepared lithium-ion battery electrolyte after sufficient drying, with an injection coefficient of 3.5g / Ah. The battery is vacuum packaged, left at 45℃ for 48h, and formed in a high-temperature fixture (the formation conditions are: temperature 45℃, pressure 210kgf, 0.1C current charging to 3.5V and standing for 60min, then 0.1C discharge to 2.3V, and so on, repeated twice). After the formation is completed, it is aged at 45℃ for 24h, and a secondary seal is performed, and then the capacity is divided conventionally to obtain a lithium-ion battery with a rated capacity of 3Ah.
[0069] Example 2-13
[0070] Examples 2-13 are achieved on the basis of Example 1 by adjusting the type of sulfur-containing additive in the electrolyte, the Fe content in the positive electrode sheet, the mass of the sulfur-containing additive added to the electrolyte corresponding to every 100g of Fe in the positive electrode sheet, the porosity of the positive electrode sheet, the porosity of the negative electrode sheet, the carbon coating amount on the surface of the lithium iron phosphate material, etc. The specific adjustment measures and detailed data are shown in Table 1. The other preparation methods are the same as those in Example 1.
[0071] Comparative Example 1
[0072] The difference between Comparative Example 1 and Example 1 is the preparation of the electrolyte: in an argon-protected glove box (water content <0.1ppm, oxygen content <0.1ppm), the solvents ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) are mixed in a mass ratio of EC:EMC:DEC=3:5:2, and lithium hexafluorophosphate (LiPF6) is added to a molar concentration of 1 mol / L (mass percentage content of 12.5%) based on the mass of the solvent, and the electrolyte is prepared after stirring. The other preparation methods are the same as those in Example 1.
[0073] Comparative Examples 2-5
[0074] Comparative Examples 2-5 are achieved on the basis of Examples 1-13 by adjusting the type of sulfur-containing additive in the electrolyte, the Fe content in the positive electrode sheet, the mass of the sulfur-containing additive added to the electrolyte corresponding to every 100g of Fe in the positive electrode sheet, the porosity of the positive electrode sheet, the porosity of the negative electrode sheet, the carbon coating amount on the surface of the lithium iron phosphate material, etc. The specific adjustment measures and detailed data are shown in Table 1. The other preparation methods are the same as those in Example 1.
[0075] In Examples 7-10 and Comparative Example 4, the sulfur-containing additive comprises 1,3-propane sultone (PS for short) and dithiothreitol (DTD), and the mass ratio of PS to DTD is 3:2. In Examples 11-12, the sulfur-containing additive comprises 1,3-propane sultone (PS for short) and dithiothreitol (DTD), and the mass ratio of PS to DTD is 1:1.
[0076] Test Method
[0077] 1. X-ray photoelectron spectrometer (XPS) test
[0078] The lithium-ion battery was discharged to 2.3V at a current of 0.1C, and the lithium-ion battery was disassembled in a glove box filled with argon to obtain the electrode sheet. The obtained electrode sheet was cut into a test sample of 8mm×8mm size, and soaked and cleaned with a low-boiling dimethyl carbonate DMC solvent for half an hour. After being completely dried, it was pasted on the XPS sample stage, with the surface of the negative electrode active material layer facing away from the current collector facing upward, and the measurement was performed without exposure to the atmosphere.
[0079] The specific test conditions and steps are as follows: single crystal spectroscopy AlKα rays are used, as for the X-ray point, an elliptical form of 1000×1750μm with an output of 10KV and 22mA is used, 284.8eV is used for neutral carbon C1s, and as for data processing such as peak differentiation, 3-point smoothing, peak area measurement, background subtraction and peak synthesis are used to calculate the atoms of each component.
[0080] 2. Pole piece porosity test
[0081] The porosity is measured by a mercury intrusion instrument, specifically: the dried electrode sample is cut into thin strips of a certain size, and the apparent volume of the electrode coating is measured using a micrometer, and the apparent volume = sample coating thickness × sample length × sample width. The electrode is then vacuum degassed, rolled up and placed in a sample cell, and the sample volume must be ensured to account for 40%-70% of the effective volume of the sample tube to ensure measurement accuracy. The pore volume of the sample is then measured using a mercury intrusion instrument, that is, the volume of mercury pressed into the sample. Porosity = pore volume / apparent volume.
[0082] 3. Initial impedance test
[0083] The lithium-ion batteries of Examples 1-13 and Comparative Examples 1-5 were subjected to a 50% SOC DCR test before cycling. The lithium-ion battery was discharged at 1C constant current to 2.3V at 25±2°C, then charged at 0.5C constant current to 3.8V, charged at 3.8V to 0.05C constant voltage, and then discharged at 1C constant current to 50% SOC, left to stand for 60 minutes, and the voltage U1 after the end of the standing was recorded, and then discharged at 2C constant current for 10s, and the voltage U2 after the discharge was recorded, and the 2C current was recorded as I, and left to stand for 60 minutes. According to the formula DCR = (U1-U2) / I, the discharge DCR of the battery at 50% SOC is calculated. .
[0084] 4. Inductively coupled plasma emission spectrometer (ICP) test
[0085] The content of metallic iron (Fe) on the surface of the negative electrode active material layer can be quantitatively analyzed by ICP.
[0086] The specific test method is as follows: the lithium-ion batteries of Examples 1-13 and Comparative Examples 1-5 after the specified cycle are disassembled in a protective atmosphere, the negative electrode plates are taken out, and washed with DMC for 3 times. After standing for several hours to allow the organic solvent to completely evaporate, the negative electrode plate powder is collected for subsequent ICP testing.
[0087] Weigh about 0.05g (accurate to 0.00001g) of the sample into a 50mL beaker, add 8.0mL of hydrochloric acid solution (concentrated hydrochloric acid and pure water are prepared in a volume ratio of 1:1), and heat on an electric furnace at low temperature to dissolve. After the sample is basically dissolved, add 5 drops of hydrogen peroxide and a small amount of water, heat until the solution stops emitting small bubbles, then remove and cool, transfer to a 100mL volumetric flask, and perform a blank experiment at the same time, and record the Fe content (ppm).
[0088] 5. Cycle capacity retention rate test
[0089] At 45°C, the lithium ion batteries of Examples 1-13 and Comparative Examples 1-5 were charged to 3.8V at 1C constant current and constant voltage, and then discharged to 2.3V at 1C constant current. After 500 cycles of charge and discharge, the capacity retention rate after the 500th cycle at 45°C was calculated according to the following formula: discharge capacity after the 500th cycle / discharge capacity in the first cycle×100%.
[0090] 6. Change rate of cell thickness after 500 cycles at 45℃
[0091] The lithium-ion batteries of Examples 1-13 and Comparative Examples 1-5 were discharged at 1C to 2.3V at 25°C, then charged at 1C to 3.8V, and then charged at a constant voltage to 0.05C at 3.8V. The thickness of the lithium-ion batteries at this time was measured using a PPG soft-pack battery thickness gauge and recorded as d0. The thickness of the battery cell after 500 cycles at 45°C was recorded as d1, and the thickness change rate was calculated as: (d1-d0) / d0×100%.
[0092] Please see Table 1 below for the test data.
[0093] Table 1
[0094]
[0095]
[0096]
[0097] By comparing the data of Examples 1-13 with Comparative Examples 1-5, it can be seen that by regulating the sulfur content in the positive electrode solid electrolyte interface film (CEI), the sulfur content in the negative electrode solid electrolyte interface film (SEI), the matching relationship between the lithium iron phosphate material in the positive electrode plate and the sulfur-containing additive in the electrolyte, so as to simultaneously satisfy 0.8≤Y1+Y2≤8.0 and 1.0≤(Y1+Y2) / Z≤3.5, under this limited condition, the film formation stability of the positive and negative electrodes can be improved, the dissolution of iron ions on the positive electrode side can be significantly reduced, and the erosion and damage of the negative electrode plate by iron ions after dissolution can be effectively avoided, and the cycle capacity retention rate of the secondary battery with lithium iron phosphate materials as the main material can be significantly improved. At the same time, the gas production problem of the secondary battery is alleviated and the impedance problem is improved.
[0098] By comparing the data of Example 1-3 with Comparative Example 1-3, it can be seen that by adjusting the mass (Z) of the sulfur-containing additive added in the electrolyte corresponding to each 100gFe in the positive electrode sheet, the values of Y1+Y2 and (Y1+Y2) / Z change accordingly. When the Z value is small, the value of Y1+Y2 is small, the Fe detection amount on the negative electrode sheet of the lithium ion battery increases significantly and the cycle capacity retention rate decreases significantly, and is accompanied by serious cyclic gas production problems. This is because the Z value is small, the value of Y1+Y2 is small, resulting in the CEI film and SEI film formed on the electrode surface being loose and porous and not dense enough, and a stable interface film cannot be formed, and the dissolution of the iron ions on the positive side cannot be prevented and the corrosion and destruction of the iron ions to the negative electrode sheet after the dissolution cannot be avoided, affecting the electrical performance and safety of the secondary battery. When the Z value is large, the value of Y1+Y2 is large, and the DCR of the lithium ion battery becomes large and the cycle capacity retention rate decreases significantly. This is because the value of Z is too large, and the value of Y1+Y2 is too large, which causes the CEI film and SEI film formed on the electrode surface to be too thick and easily unevenly distributed. An excessively thick interface film will bring a higher interface impedance (DCR), thereby deteriorating the kinetic performance of the secondary battery. At the same time, an unevenly distributed interface film is also prone to cause lithium plating problems in the battery cell, resulting in a decrease in the performance of the secondary battery, a significant decrease in the cycle capacity retention rate, and even affecting the safety performance of the secondary battery.
[0099] By comparing the data of Examples 7-9 with Comparative Example 4, it can be seen that by adjusting the porosity ε1 and ε2 of the positive and negative electrode sheets, the values of Y1+Y2 and (Y1+Y2) / Z change accordingly. When the porosity of the positive and negative electrode sheets is too small, the values of Y1+Y2 and (Y1+Y2) / Z are too small, the cycle capacity retention rate of the lithium-ion battery decreases significantly and the problem of cyclic gas production is serious. This is because the porosity of the positive and negative electrode sheets is too low, which affects the infiltration of the electrolyte, resulting in too low sulfur content in the CEI membrane and SEI membrane, and at the same time increasing the difficulty of lithium ion conduction.
[0100] Although some exemplary embodiments of the present application have been illustrated and described, the present application is not limited to the disclosed embodiments. On the contrary, those skilled in the art will recognize that some modifications and changes may be made to the described embodiments without departing from the spirit and scope of the present application as described in the appended claims.
Claims
1. A secondary battery, characterized in that: The secondary battery comprises a positive electrode sheet, a negative electrode sheet and an electrolyte, wherein the positive electrode sheet comprises a positive electrode active material layer and a positive electrode solid electrolyte interface film located on the surface of the positive electrode active material layer; the negative electrode sheet comprises a negative electrode active material layer and a negative electrode solid electrolyte interface film located on the surface of the negative electrode active material layer; The positive electrode active material layer includes a positive electrode active material, the positive electrode active material includes a lithium iron phosphate material, and the electrolyte includes a sulfur-containing additive, wherein every 100g of Fe corresponds to Z g of the sulfur-containing additive; According to the test using an X-ray photoelectron spectrometer, the mass percentage of sulfur in the positive electrode solid electrolyte interface film is Y1%, and the mass percentage of sulfur in the negative electrode solid electrolyte interface film is Y2%; The secondary battery satisfies the following requirements: (1) 0.8≤Y1+Y2≤8.0; and (2) 1.0≤(Y1+Y2) / Z≤3.
5.
2. The secondary battery according to claim 1, characterized in that: The secondary battery further satisfies at least one of the following conditions: (1) 1.0≤Y1+Y2≤6.0; (2)1.5≤(Y1+Y2) / Z≤3.
0.
3. The secondary battery according to any one of claims 1 or 2, characterized in that: The secondary battery further satisfies at least one of the following conditions: (1)0.1≤Y1≤2.5; (2)0.3≤Y2≤6.0; (3)0.1≤Z≤5.0。 4. The secondary battery according to claim 3, characterized in that: The secondary battery further satisfies at least one of the following conditions: (1)0.3≤Y1≤2.0; (2)0.5≤Y2≤5.0; (3)0.3≤Z≤4.0。 5. The secondary battery according to any one of claims 1 or 2, characterized in that: The sulfur-containing additive includes at least one of sulfonate, sulfate, and sulfite.
6. The secondary battery according to claim 5, characterized in that: The sulfonate ester includes at least one of methylene methanedisulfonate, 1,3-propane sultone, 1-propylene-1,3-sultone, 1,4-butane sultone and methylene methanedisulfonate; and / or, The sulfate ester includes at least one of vinyl sulfate, 4-methylethylene sulfate, 4-ethylethylene sulfate, 4-propylethylene sulfate and propylene sulfate; and / or, The sulfite includes at least one of ethylene sulfite, dimethyl sulfite and diethyl sulfite.
7. The secondary battery according to any one of claims 1 or 2, characterized in that: The lithium iron phosphate material includes Li x Fe y R (1-y) At least one of PO4 materials, wherein R includes at least one of Mn, Co, Ti, Mg, Ca, Cr, Cu, Ni, V, Mo, Zn, Al, B and Nb elements, 0.05≤x≤1.2, 0<y≤1.
8. The secondary battery according to any one of claims 1 or 2, characterized in that: The secondary battery further satisfies at least one of the following conditions: (1) The surface of the lithium iron phosphate material has a carbon coating layer; based on the mass of the lithium iron phosphate material, the mass percentage of the carbon coating layer is 1% to 3%; (2) The porosity of the positive electrode sheet is ε1, which satisfies: 22%≤ε1≤42%; (3) The porosity of the negative electrode plate is ε2, satisfying: 28%≤ε2≤45%.
9. The secondary battery according to any one of claims 1 or 2, characterized in that: The negative electrode active material layer includes a negative electrode active material, and the negative electrode active material includes at least one of a silicon-based material, a carbon-based material, a tin-based material, a phosphorus-based material and metallic lithium; wherein the silicon-based material includes at least one of silicon, a silicon alloy, a silicon oxide compound and a silicon carbon compound; the carbon-based material includes at least one of graphite, soft carbon, hard carbon, carbon nanotubes and graphene; the tin-based material includes at least one of tin, tin oxide and a tin alloy; the phosphorus-based material includes at least one of phosphorus and a phosphorus complex; and / or, The electrolyte also includes a non-aqueous solvent and a lithium salt, wherein the non-aqueous solvent includes at least one of a chain carbonate compound, a cyclic carbonate compound and a carboxylate compound; and the lithium salt includes at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, trifluorosulfonyl lithium, lithium bis(oxalatoborate), lithium bis(fluoromalonate)borate and lithium difluorooxalatoborate.
10. A device, characterized in that: The device includes the secondary battery according to any one of claims 1 to 9.
Citation Information
Patent Citations
Lithium ion battery
CN115548422A
Lithium ion battery electrolyte, preparation method and application thereof
CN115986209A